Collocational Processing in Light of the Phraseological Continuum Model: Does Semantic Transparency Matter?. Issue 2 (6th October 2015) - Gyllstad, Henrik; Wolter, Brent
Abstract: The present study investigates whether two types of word combinations (free combinations and collocations) differ in terms of processing by testing Howarth's Continuum Model based on word combination typologies from a phraseological tradition. A visual semantic judgment task was administered to advanced Swedish learners of English ( n = 27) and native English‐speaking controls ( n = 38). Reaction times and error rates were recorded for free combinations, collocations, and baseline items. There was a processing cost for collocations compared to free combinations, for both groups of participants. This cost likely stems from the semantically semi‐transparent nature of collocations as they are defined in the phraseological tradition. Furthermore, phrasal frequency based on corpus values also predicted reaction times. These results lend initial support to the Continuum Model from a processing perspective and suggest that degree of semantic transparency together with phrasal frequency plays an important role in collocational processing. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki